Pengaruh entrepreneurial creativity terhadap keberhasilan startup pada bisnis startup the greater hub - Razati, M.Si, Girang -; Nuryanti, B Lena; Utama, Fajar Nugraha (Journal of Business Management Education (JBME), 2020)
The purpose of this research is to test and analyze the entrepreneurial creativity and startup success on The Greater Hub startup business. Population in this research is The Greater Hub startup business with the number of respondents as many as 30 reviewers. The method used in this research is explanatory survey to explore the problem situation. The sampling technique used is non probability sampling by using path analysis. Results entrepreneurial creativity generate positive influence on startup success.